PENGARUH PENYULUHAN KONSUMSI MAKANAN KARIOGENIK PADA IBU DAN ANAK TERHADAP KEPARAHAN KARIES SISWA TAMAN KANAK-KANAK (Kajian Pada Siswa Taman Kanak-Kanak di Kecamatan Kasihan Kabupaten Bantul) - Uswatun Nisaa' Arum Darjono; Sri Widiati; Al. Supartinah (Odonto : Dental Journal, 2015)
Background: Prevention of caries in preschool children is influenced by role of mothers. In reality lots of mothers do not pay much attention in maintaining the children's teeth. Purpose: The study aimed to find out the effect of socialization on cariogenic food consumption in mothers and children to dental and caries severity of children at kindergartens at Subdisctrict of Kasihan District of Bantul. Method: The study was a quasi experiment with Two Group Pre-Test Post-Test Design. Samples were determined through cluster sampling technique, comprising as many as 136 pairs of mothers and children in three kindergartens at the area of Subdistrict of Kasihan, District of Bantul. The study was focused on the effect of socialization on cariogenic food consumption to knowledge of children, knowledge of mothers, mothers' behavioral tendencies and dental and oral health statcaries severity of children. Data the knowledgeof children, knowledge of mothers and mothers' behavioral tendencies were assessed using questionaire, and CIS as caries severity index and analyzed using paired t-test and independent t-test. Conclusion: Socialization in group of mothers and children increased knowledge of children, knowledge of mothers, behavioral tendencies of mothers than in group of children. Socialization in group of mothers and children and group of children did not decrease severity of dental caries